2019
DOI: 10.1371/journal.pone.0215478
|View full text |Cite
|
Sign up to set email alerts
|

Wild and farmed salmon (Salmo salar) as reservoirs for infectious salmon anaemia virus, and the importance of horizontal- and vertical transmission

Abstract: The infectious salmon anaemia virus (ISAV) is an important pathogen on farmed salmon in Europe. The virus occurs as low- and high virulent variants where the former seem to be a continuous source of new high virulent ISAV. The latter are controlled in Norway by stamping out infected populations while the former are spreading uncontrolled among farmed salmon. Evidence of vertical transmission has been presented, but there is still an ongoing discussion of the importance of circulation of ISAV via salmon brood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Nowadays it is known that the highest prevalence corresponds to the apathogenic variant HPR0, which is present in practically all countries that grow Atlantic Salmon [ 27 ], and sporadically (2 to 3 cases with HPRΔ per year in Chile) due to deleterious variants that cause the disease. The current regulations in Chile do not allow the treatment of animals infected with pathogenic variants of the virus and sanitary slaughter is enforced; however, animals infected with apathogenic variants (HPR0) can continue in the production cycle under intensive surveillance being aware that the situation can change at any time [ 8 , 28 ]. The results obtained in our study, show that the peptides can decrease the viral load of the variants tested (HPR3a and HPR14a).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it is known that the highest prevalence corresponds to the apathogenic variant HPR0, which is present in practically all countries that grow Atlantic Salmon [ 27 ], and sporadically (2 to 3 cases with HPRΔ per year in Chile) due to deleterious variants that cause the disease. The current regulations in Chile do not allow the treatment of animals infected with pathogenic variants of the virus and sanitary slaughter is enforced; however, animals infected with apathogenic variants (HPR0) can continue in the production cycle under intensive surveillance being aware that the situation can change at any time [ 8 , 28 ]. The results obtained in our study, show that the peptides can decrease the viral load of the variants tested (HPR3a and HPR14a).…”
Section: Discussionmentioning
confidence: 99%
“…Second, Madhun et al (2018) also document the presence of piscine ortho reo virus (PRV) in returning wild adult Atlantic salmon in Norway, and that the frequency of infection increased with body size and displayed no geographic signal, suggesting infection was occurring between escapees and wild salmon at marine feeding areas. Nylund et al (2019) report that infectious sal mon anemia virus (ISAV) variants in farmed sal mon are increasing in prevalence in the wild consistent with horizontal transmission from farmed sal mon to wild populations. Similarly, Garseth et al (2013) examine pathogen transfer between wild and farmed salmon using analysis of protein coding sequences in PRV in Norway and suggest occurrence in the wild is due to long distance transmission likely associated with the aquaculture industry.…”
Section: Ecological and Non-reproductive Genetic Changes Through Disementioning
confidence: 99%
“…Viral diseases constitute the dominate disease vector affecting aquaculture. However, direct evidence of disease transfer from aquaculture to wild conspecifics is limited (but see Nylund et al 2019). Yet, horizontal transmissions have been documented to be introduced via aquaculture farms and subsequently detected in wild populations (Nylund et al 2019) and recaptured escaped farmed salmon have been observed with high densities of pathogens in or near rivers (Madhun et al 2017).…”
Section: Conflicts Between Wild Atlantic Salmon and Aquaculturementioning
confidence: 99%
“…However, direct evidence of disease transfer from aquaculture to wild conspecifics is limited (but see Nylund et al 2019). Yet, horizontal transmissions have been documented to be introduced via aquaculture farms and subsequently detected in wild populations (Nylund et al 2019) and recaptured escaped farmed salmon have been observed with high densities of pathogens in or near rivers (Madhun et al 2017). Still, broad scale infection rates are largely unknown due to the difficulty of detecting infected individuals as they tend to be less catchable and more susceptible to predation events (Bakke and Harris 1998).…”
Section: Conflicts Between Wild Atlantic Salmon and Aquaculturementioning
confidence: 99%